Screening of brewing yeast β-lyase activity and release of hop volatile thiols from precursors during fermentation - Michel, Maximilian; Haslbeck, Korbinian; Ampenberger, Friedrich; Meier-Dörnberg, Tim; Stretz, Dominique; Hutzler, Mathias; Coelhan, Mehmet; Jacob, Fritz; Liu, Yang (BrewingScience, 2019)
Volatile thiols derived from some hop varieties largely impact the flavour of beer even though they are found in relatively low concentrations. The described thiols are further present in slightly higher concentration as flavourless cysteinylated precursors in hops. Yeasts have been found to release these thiols via the enzyme β-lyase and therefore increase the amount of flavour-active thiols. To investigate the β-lyase activity of brewing yeasts and increase the volatile thiol content derived from hops in beer, 148 strains of three different species (Saccharomyces pastorianus, S. cerevisiae, Torulaspora delbrueckii) were screened. The IRC7 genotype of each strain was investigated as this gene was described as having a big impact on the β-lyase activity of S. cerevisiae wine yeasts. A selective media was also used to detect yeast strains with increased β-lyase activity. Fermentations were then performed to show the impact of six yeast strains on the content of the volatile thiols 3-mercaptohexanol and 4-mercapto-4-methylpentan-2-one. A very homogeneous distribution of the IRC7 gene was found for the investigated brewing yeasts. The applied selective medium showed low predictability for β-lyase activity but needs further investigations. Transfer rates for 3-mercaptohexanol were found to be above 1000?% in the finished beers. The rise in 4-mercapto-4-methylpentan-2-one was found to be significantly influenced by the yeast strain and indicated the presence of other precursors or a potential biotransformation.